A Study of Systemic Functional Linguistics: Political Ideology of Donald Trump and Hillary Clinton in First Presidential Debate - Alda Fitriani Suwandi; Muhammad Thoriqussuud (Journal of English Education and Teaching, 2021)
This journal article discusses how to reveal the ideology through two approaches, those are transtivity process by MAK Halliday and the theoretical framework in Critical Discourse Analysis by Fairclough. This journal article investigates Donald Trump and Hillary Clinton ideology, then compares their ideology who is more prominent. Before revealing their ideology, the researcher compares the transtivity process of both candidates and finds that Donald Trump has 281 clauses consist of transtivity process, while Hillary Clinton has 203 clauses consist of transtivity process. The differences of the total numbers of transtivity process, it also reflects to the tendency of ideology. It has shown that Trump has 60% to the citizen involvement rather than Hillary has 52%. Then, in the aspect of national priority, Hillary has the highest tendency that is 16% rather than Trump has 6%. The third aspect is policy of law Hillary also has the highest tendency that is 11% than Trump only 7%. In the aspect of equality in democracy ideology, Trump gets 7% while Hillary gets 0%. In the last aspect, is national unity Trump gets 20% tendency than Hillary gets 19%. Finally, the researcher concludes that Donald Trump’s ideology is the most prominent than Hillary Clinton.